Endocrine disruption in the sub Antarctic fish Patagonotothen tessellata (Perciformes, Notothenidae) from Beagle Channel associated to anthropogenic impact - Ferreira, María Florencia; Lo Nostro, Fabiana Laura; Fernandez, Daniel Alfredo; Genovese, Griselda (Marine Environmental Research)
Situated in the sub-Antarctic region, Beagle Channel represents a unique marine ecosystem due to the connection between the Pacific and the Atlantic Oceans, and its proximity to the Antarctic Peninsula. Ushuaia city, the biggest settlement on the channel, exerts an increasing anthropogenic pressure by discharges of urban and industrial effluents. In the present work, we use Patagonotothen tessellata, one of the most abundant and widespread species in the channel, as a bioindicator species in order to evidence anthropic impact from Ushuaia Bay and surrounding areas. We first analyzed and characterized real time gene expression of androgen receptor, estrogen receptor and different forms of vitellogenin (VTG), under laboratory conditions. This was achieved by induction with estradiol of P. tessellata males. Then, the selected genes were used as biomarkers for an environmental biomonitoring study. Morphometric indices and circulating sex steroids (estradiol and testosterone) were also quantified in male fish collected from different sites. The qPCR analysis showed that vtgAb form is more inducible than vtgAa or vtgC forms after estrogen induction. The field survey revealed the up-regulation of vtgAb and the androgen receptor in fish from sites with higher anthropogenic influence. Sex steroids followed seasonal variations according to their reproductive cycle, with higher levels of estradiol and testosterone in winter and summer seasons. The use of biomarkers such as gene expression of VTG demonstrates that fish from Ushuaia Bay are likely to be exposed to endocrine disrupting compounds. To our knowledge, this research is the first attempt to assess the endocrine disruption associated to anthropic impact in a widespread fish of the Beagle Channel and contributes to a better understanding of the reproductive physiology of sub Antarctic ichthyofauna. Fil: Ferreira, María Florencia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de ...